A Dél-Dunántúli kisvárosok a fejlesztési tervek tükrében (The South-Transdanubien Small Towns in the Light of the Development Plans) - Réka Horeczki (DETUROPE)
The South Transdanubien region is among the 20 most disadvantaged region of the European Union, that shows a significant decrease compared to previous years. I think any professional research can we rationale, that to change this situation, do some substantive attept. I intend to shed light on the prospects/possibilities that this small town can have in the future; and I also want to find out whether it has developmental possibilities originated in the past yet adaptable to the current situation. When the development plans have been realized these town and neighborhoods has a decreasing migration and stabilized small towns culture. The aim of the present study is to present the long-term developmental laws and characteristic features that heavily influence the economic, social and political life of the South Transdanubian region via the developments plan of the small towns. In addition to the urban development plans I analyzed the statistical data and the associations scheme.